MANAGEMENT OPTIMISATION OF DIGITAL-BASED LEARNING IN MADRASAH - Siswahyuningsih, Zahrotunnisa; Tanzeh, Ahmad (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
This scientific article discusses madrasah management's responsiveness to globalisation through the implementation of digital-based learning at MTsN 1 Tulungagung. The purpose of this study is to analyse the planning, implementation, and evaluation processes in improving the quality of learning, especially digital-based learning. This study employs a qualitative approach, using data collection methods including interviews, observation, and documentation. The data were analysed through condensation, presentation, and verification. Data validity was ensured through tests of credibility, transferability, dependability, and confirmability. The results of the study show that planning includes alignment with the madrasah's vision, mission, and objectives, supported by coordination meetings, the preparation of facilities and infrastructure, improvements in teacher competence, and socialisation with parents and prospective students. The implementation of digital learning was successful due to the synergy between available facilities and infrastructure and the presence of competent, well-qualified human resources. Evaluations were conducted incidentally and periodically at the end of the semester through reflection and Computer-Assisted Test (CAT)-based examinations. There were obstacles to implementing digital-based learning, namely, limited facilities and infrastructure, as well as misconceptions about it. The study concluded that strategic management can enhance the quality of digital learning, offering essential implications for educational institutions as they adapt to technological advances.